A comparative review of the epidemiology of mental disorders in Australia and India. (6th June 2022) - Pai, Nagesh; Vella, Shae‐Leigh; Castle, David
Abstract: Mental illness and substance use disorders have been increasing worldwide. Mental illness has a significant impact upon the lives of the individual as well as their loved ones. Mental disorders are known to result in a high level of disability. This article provides a comparative review of the epidemiology of mental disorders in Australia and India, summarizing and comparing prevalence rates in both countries based upon available data. Overall, it is evident that Australia has higher prevalence rates of mental disorders than India, across most diagnostic groups. Australia has the highest prevalence of anxiety disorders whereas India has the highest prevalence of substance use disorders; including tobacco use disorders. The next most prevalent mental disorders in India are depressive disorders. However, there are demographic parameters such as gender and age as well as service‐provision differences across the countries that need to be factored into any interpretation of the data. There are also problems associated with different diagnostic instruments with language and cultural nuances that may impact comparisons. We suggest that a joint epidemiological survey between the two countries would help better understand and delineate the key similarities pertaining to the epidemiology of mental disorders in Australia and India. This will in turn assist with the development of policy and treatment of mental disorders.